2009
DOI: 10.1038/tpj.2009.20
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of EGF+61G>A and TGFB1+869T>C functional polymorphisms in the time to androgen independence and prostate cancer susceptibility

Abstract: Proliferative mechanisms involving the epidermal growth factor (EGF) and transforming growth factor beta (TGF-b 1 ) ligands are potential alternative pathways for prostate cancer (PC) progression to androgen independence (AI). Thus, the combined effect of EGF and TGFB1 functional polymorphisms might modulate tumor microenvironment and consequently its development. We studied EGF þ 61G4A and TGFB1 þ 869T4C functional polymorphisms in 234 patients with PC and 243 healthy individuals. Intermediate-and highprolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
(57 reference statements)
0
21
0
Order By: Relevance
“…The TGFB1+869T>C polymorphism was analyzed by allelic discrimination using 7300 real-time polymerase chain reaction system (real-time PCR) (Applied Biosystems, Foster City, CA, USA), as described in a previous report (Teixeira et al 2009). Real-time PCR was performed in a 6-l reaction mixture, containing 1£ Master Mix (Applied Biosystems, Foster City, Ca, EUA), with 1£ probes (TaqMan assay C__22272997_10__, Applied Biosystems, Foster City, CA, EUA) and 90 ng of the DNA sample.…”
Section: Tgfb1+869t>c Genotypingmentioning
confidence: 99%
“…The TGFB1+869T>C polymorphism was analyzed by allelic discrimination using 7300 real-time polymerase chain reaction system (real-time PCR) (Applied Biosystems, Foster City, CA, USA), as described in a previous report (Teixeira et al 2009). Real-time PCR was performed in a 6-l reaction mixture, containing 1£ Master Mix (Applied Biosystems, Foster City, Ca, EUA), with 1£ probes (TaqMan assay C__22272997_10__, Applied Biosystems, Foster City, CA, EUA) and 90 ng of the DNA sample.…”
Section: Tgfb1+869t>c Genotypingmentioning
confidence: 99%
“…In addition, increasing evidence suggests that genetic markers may be independent predictors of outcome in PCa with various SNPs predicting decreased progression-free and overall survival [3][4][5][6]. Data presented here show that the homozygous T genotype Tallele of HIF1A +1772 C>T is associated with increased relapsing after ADT, whereas the T allele is prone to higher risk for having distant metastasis, still after adjustment for empirical covariates (adjusted by Gleason grade, clinical stage and PSA P 20 ng/ml for the risk of metastasis; and by Gleason grade, clinical stage, PSA P 20 ng/ml, definitive therapy and existence of metastases at the time of hormonal castration initiation for the risk of disease recurrence after ADT).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new strategies to help clinicians distinguish between lethal and indolent prostate cancer are needed. Recent findings indicate that genetic variants may predispose to more aggressive prostate cancer [3][4][5], which is supported by epidemiological studies that propose genetic background influences cancer prognosis [6][7][8]. Recent genome-wide association studies (GWAS) revealed numerous genetic variants associated with prostate cancer risk, although only little discriminatory ability was shown for fatal forms of the disease [9].…”
Section: Introductionmentioning
confidence: 93%
“…To date, several SNVs in TGF-β1 have been identified as PCa-susceptibility variants, some of them also associated with PCa aggressiveness [118][119][120][121][122][123]. The studies on the most of the chronic inflammation-related genes provided conflicting results [117].…”
Section: Chronic Inflammation and Angiogenesismentioning
confidence: 99%